Will China's Free Teacher Education Policy address teacher shortages in rural schools or reproduce existing inequality?. Issue 5 (3rd July 2020) - Qian, Hong; Youngs, Peter; Hu, Sihua; Prawat, Xueying Ji
ABSTRACT: China's Free Teacher Education Policy (FTEP) was initiated in 2007 in response to concerns about university tuition increases and teacher shortages in rural provinces. In this paper, the authors draw on interview data from eight FTEP graduates/teaching candidates and eight teacher educators from five FTEP universities to examine the extent to which and ways in which this policy seems to provide (a) financial support to prospective university students from low-income families and (b) teachers for rural schools in these provinces. Their results indicate that the FTEP has made higher education at top-ranked universities more accessible for students from low-income families, which promotes social mobility for those students. However, their results also suggest that most FTEP graduates prefer to teach in more affluent city schools rather than rural schools. Therefore, the policy is likely to have much less impact on improving educational opportunity or social mobility for students in such rural schools.